Three decades of wildlife-vehicle collisions in a protected area: Main roads and long-distance commuting trips to migratory prey increase spotted hyena roadkills in the Serengeti. (March 2023) - Naciri, Marwan; Planillo, Aimara; Gicquel, Morgane; East, Marion L.; Hofer, Heribert; Metzger, Sonja; Benhaiem, Sarah
Abstract: Vehicles kill many wild animals worldwide, including in protected areas, where the impacts of roads are increasing due to road development, the rise of human population at their boundaries, and the growing interest in wildlife tourism. Yet, knowledge on the factors influencing wildlife roadkills within protected areas is limited, particularly for large carnivores. Here, we investigated spotted hyena ( Crocuta crocuta ) roadkills inside a protected area, the Serengeti National Park, Tanzania, between 1989 and 2023 (n = 104). We examined spatial determinants of hyena roadkills using a generalized linear model, temporal and spatiotemporal patterns in hyena roadkills, and the effect of age, sex, and social status on hyena mortality due to vehicles. Roadkills were more likely on main roads and the locations and number of roadkills varied according to seasonal changes in the locations of vast migratory ungulate herds, which are the main prey of hyenas. Adult females, who travel the most to forage on these herds, suffered the highest levels of road mortality. Road mortality was independent from social status among females. Our results indicate that roadkill patterns were shaped by both road characteristics, as incidence was substantially higher on main roads, and large-scale seasonal changes in the location of migratory prey. Further, the incidence of hyena roadkills was exacerbated by long-distance 'commuting' trips to areas containing large aggregation of migratory herbivores. Our findings provide new insight on ecological and individual factors modulating roadkill incidence in a large carnivore.